Creative Abilities of Students and Teaching for Creativity; A Comparative Study of Public and Private Schools of Lahore City - Samra Bashir; Humera Amin; Syeda Beenish Batool (Journal of Arts & Social Sciences, 2020)
This study was designed to explore the creative thinking abilities of primary school students in Pakistan. The study also explored teachers’ perceptions about the creative abilities of students. Multistage sampling was applied to select the sample. Four primary schools (2 from public sector and 2 from private sector) from Lahore city were selected randomly to collect the data. 100 students and 100 teachers were selected by applying cluster sampling. Torrance Tests of Creative Thinking (TTCT) were conducted to identify the abilities of students related to creativity. A questionnaire was developed to identify the perceptions of teachers regarding the development of creativity among students. Reliability of the questionnaire was .855. Independent sample t-test was applied to identify the difference between the creativity of public and private sector school students and perceptions of teachers. Findings show that students who were studying in private schools are more competent in creative writing and have more expressive ability than public school students. Teachers of private schools were using the methods and techniques more effectively for teaching creativity. The study has important implications for the development or otherwise of creativity in primary schools in Pakistan.